Endophytic Bacteria From Banana Plants Improves The Growth of Rice (Oryza sativa) and Maize Plants (Zea mays) - Sidiq, Yasir; Silviani, Defina Anggita; Rahayu, Triastuti; Saputra, Alanindra; Wahibah, Ninik Nihayatul; Widianto, Donny (Al-Kauniyah: Jurnal Biologi, 2025)
AbstractFive isolates of endophytic bacteria from the roots of klutuk and ambon banana plants produce indole acetic acid (IAA) hormone. However, the evidence of its potential as Plant Growth Promoting Bacteria (PGPB) has not been observed. Therefore, this study aims to determine the effect of bacterial isolate to increase the growth of rice and maize plants. The growth rates of bacterial isolates were measured before the inoculation into the plant root. The root inoculation was performed following a complete randomized design. Root inoculation was carried out using 5 isolates of endophytic bacteria in rice and maize plant seedlings, and the process was repeated 15 times (n=15). The growth of rice and maize plants was monitored from 1st day after planting (dap) to the 14th dap. The collected data were analyzed by student t-test with a significant level of 5% (a= 0.05). The results showed that the logarithmic phase of all isolates was reached at 4 to 16 hours and K10, K25, K35, K111, and A41 isolates increased the height of plants while the K111 isolate can significantly increase the plant height compared to the control. This experiment revealed that the endophytic bacteria from banana plants increase the rice and maize plant’s growth.AbstrakLima isolat bakteri menghasilkan hormon indole acetic acid (IAA) yang berpotensi memacu pertumbuhan tanaman. Namun, bukti empiris potensinya sebagai Plant Growth Promoter Bacteria (PGPB) belum didapatkan. Penelitian ini bertujuan untuk mengetahui pengaruh isolat bakteri terhadap peningkatan pertumbuhan padi dan jagung. Penelitian ini menggunakan metode eksperimen dengan desain rancangan acak lengkap dan setiap perlakuan diulang 15 kali (n= 15). Hasil pertumbuhan tanaman yang diinokulasi dengan isolat bakteri masing-masing dibandingkan dengan perlakuan kontrol. Sebelum perlakuan, tingkat pertumbuhan bakteri endofit diukur sehingga didapatkan fase logaritmik yang cocok untuk dilakukan inokulasi ke akar tanaman. Setelah perlakuan, pertumbuhan tanaman padi dan jagung dipantau dari hari ke-1 setelah tanam (hat) sampai dengan ke-14 hat. Data dianalisis dengan uji t dengan taraf signifikan 5% (α= 0,05). Hasil penelitian menunjukkan bahwa 5 isolat yang berasal dari tanaman pisang mengalami fase logaritmik pada masa inkubasi 4 hingga 16 jam dan semua isolat bakteri meningkatkan tinggi tanaman serta isolat K111 dapat meningkatkan tinggi tanaman secara signifikan dibandingkan dengan kontrol. Penelitian ini mengungkapkan kemampuan bakteri endofit dari tanaman pisang untuk meningkatkan pertumbuhan tanaman.